Research on long-term care insurance system under the concept of continuity nursing (延续性护理理念下的长期护理保险体系研究) - CUI Xin (崔欣); GAO Dongqing (高冬青); KOU Lin (寇琳); LUO Yanbin (罗艳彬); AN Rongrong (安荣荣); SUN Xiaoshuang (孙潇爽) (中西医结合护理)
Starting from the concept and practice of continuity nursing, this paper focuses on the development of long-term care insurance that is conducive to the popularization and application of continuity nursing. This paper analyzes deeply about insurance system construction, nursing needs assessment, nursing insurance elements setting and other aspects, draws on international experience, explores optimization paths, and puts forward scientific suggestions for further improving long-term care insurance system in China. (本文从延续性护理理念与实践出发, 研究有利于延续性护理普及应用的长期护理保险发展问题。在保险体系构建、护理需求评估、护理保险要素设置等多个方面进行深入剖析与思考, 借鉴国际经验, 探索优化路径, 为进一步完善适合中国国情的方案提出科学建议。)